1362 ANTICHOLINERGIC PRESCRIBING HABITS AND ITS ASSOCIATIONS IN A COMMUNITY POPULATION OF PEOPLE LIVING WITH DEMENTIA. (16th January 2023) - Curtis, F; Li, L; Kolanko, M; Lai, H; Daniels, S; True, J; Del Giovane, M; Golemme, M; Lyall, R; Raza, S; Hassim, N; Patel, A; et al.
Abstract: Introduction: Many commonly prescribed medications have inadvertent anticholinergic effects. People with Dementia (PwD) are more vulnerable to these effects and at risk of adverse outcomes, the risk being higher with a greater degree of anticholinergic exposure. We investigated prescribing patterns and Anticholinergic burden (ACB) in a cohort of community-dwelling older adults with dementia and aimed to explore the effect of ACB on cognition, mood, and quality of life(QoL). Method: The medication and demographic information for 87 (39 female) community-dwelling PwD were obtained from Electronic Care Summaries. We used the German Anticholinergic Burden Scale (GABS) to measure ACB. Additionally, we investigated associations between ACB and cognitive (ADAS-Cog), functional (BADL) and QoL (DemQoL) assessments. Results: 28.7% of participants had a clinically significant score (ACB> 2). The most commonly prescribed medications with ACB were Lansoprazole(18.3%), Mirtazapine(12.6%) and Codeine(12.6%). ACB was higher in males and negatively correlated with age, r (87)=-.21, p =.03. There was no association between ACB and cognition, QoL, functional independence, and neuropsychiatric symptoms. Over six months, PLWD with no ACB had a greater negative change in neuropsychiatric symptoms[ t (18)=2.27, p =.04] and functional independence[ t (23)=-3.8, p =.001], indicating greater dependence and worsening neuropsychiatric symptoms. Conclusion: A third of PLWD in the community had clinically significant ACB. No ACB was associated with worsening neuropsychiatric symptoms and functional dependence over a six-month period. Community prescribers should consider regular medication reviews with PLWD and carers to ensure medications are prescribed safely and appropriately.